2012
DOI: 10.1002/adsc.201200253
|View full text |Cite
|
Sign up to set email alerts
|

A General Approach to Substituted Benzimidazoles and Benzoxazoles via Heterogeneous Palladium‐Catalyzed Hydrogen‐Transfer with Primary Amines

Abstract: The synthesis of benzimidazoles starting from o-phenylenediamines and amines in the presence of palladium on charcoal as catalyst is reported. Under microwave dielectric heating it is possible to use a tertiary, a secondary, and even a primary amine as the substrate for a palladium-mediated process to get 2-substituted or 1,2-disubstituted benzimidazoles, depending on the nature of the o-phenylenediamine employed. Primary amines are the most suitable reagents for the atom economy of the overall process that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…13d Narender et al15a and Nguyen et al 15b,c independently reported a few metal-free procedures for synthesis of benzimidazoles and benzothiazoles from benzylamines and 2-amino/mercaptoanilines. Scheme 1c).…”
mentioning
confidence: 99%
“…13d Narender et al15a and Nguyen et al 15b,c independently reported a few metal-free procedures for synthesis of benzimidazoles and benzothiazoles from benzylamines and 2-amino/mercaptoanilines. Scheme 1c).…”
mentioning
confidence: 99%
“…With this promising data in hand, we have also found that by using 0.35 equivalents of Et 3 N there was no impact on the conversion (Fig. 2 , entry 2), proving that two of the three groups of the tertiary amine could be transferred to 1a 25 . Similar results were obtained irradiating for 60, 30 or even only 20 minutes (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…2 , entry 6) or using toluene as the solvent for 90 minutes (Fig. 2 , entry 7) 25 lower conversions were observed. Irradiation of 1a in GVL led to good reaction yields also when the catalyst amount was reduced to 5 or even 2.5 mol% (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The reaction occurred in toluene under MW dielectric heating with crotonitrile as a hydrogen acceptor, allowing the direct transformation of tertiary amines into benzimidazoles [95]. Primary amines (such as 131 in Scheme 38) can also be used in the presence of acetic acid as an additive in a synthesis of 1(H)-benzimidazoles, 1-susbtituted benzimidazoles, and benzoxazoles (such as 133 in Scheme 38) [96]. The possibility of oxidizing amine to imines has also been exploited in the synthesis of heterocycles through an overall hydrogen transfer oxidative process.…”
Section: Pd/c In Oxidative Hydrogen Transfer Reactionsmentioning
confidence: 99%